Reproductive Of Mice (Mus musculus) AS A Model TO Study Genotype Environtment Interaction (GEI) Of Dairy Cattle Reproductive Characters In The Tropics - Paridjata Westra (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2008)
.